Pengaruh Lokasi, Promosi, dan Lokasi Terhadap keputusan Pembelian Rumah Kpr Subsidi - Muhammad Habib Rizky; Satria Mirsya Affandy Nasution (-, 2023)
The purpose of this research is to determine and analyze the influence of price on purchasing decisions. To find out and analyze promotions on purchasing decisions. To find out and analyze location on purchasing decisions. To find out and analyze the influence of price, promotion and location on the decision to purchase a subsidized KPR house at PT Indah Cahaya Rizky. In this study using associative approach to determine the relationship of each variable. The data is presented in the form of quantitative data, namely testing and analyzing the data by calculating numbers and then drawing conclusions and testing. In this study, the object studied was the Subsidized KPR House at PT Indah Cahaya Rizky with an unknown population and a sample of 56 people with sampling using theLemeshow formula. The results of this research are that price has a significant effect on purchasing decisions. Promotion has a significant effect on purchasing decisions. Location has a significant influence on purchasing decisions. Andprice, promotion and location have a significant influence on the decision to purchase a subsidized KPR house at PT Indah Cahaya Rizky.